2007
DOI: 10.1097/01.ten.0000257437.32997.af
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Ultrasonography in Detecting Thyroiditis

Abstract: Ultrasonography (USG) is frequently used to diagnose thyroiditis. The accuracy of this diagnosis, however, is unclear. This study was performed to determine the sensitivity and specificity of USG in detecting thyroiditis. Three hundred thyroid patients were enrolled in the study. The diagnosis of thyroiditis by USG and by antithyroid peroxidase (anti-TPO) antibodies was compared. Thyroiditis was determined in 75 of 300 thyroid patients by USG and in 180 of 300 patients by anti-TPO antibody measurement. Anti-TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Furthermore, Tabur et al found that sonography has high specificity (90%) and low sensitivity (35%) in the diagnosis of thyroiditis. [30] Furthermore, in the current study, coarse echotexture as a sign of HT had a sensitivity of 81.54%, a result similar to those of Patel et al , who found that diffuse heterogeneity had a sensitivity of 88.2% in the diagnosis of HT. [31]…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Tabur et al found that sonography has high specificity (90%) and low sensitivity (35%) in the diagnosis of thyroiditis. [30] Furthermore, in the current study, coarse echotexture as a sign of HT had a sensitivity of 81.54%, a result similar to those of Patel et al , who found that diffuse heterogeneity had a sensitivity of 88.2% in the diagnosis of HT. [31]…”
Section: Discussionsupporting
confidence: 89%
“…Grayscale thyroid sonography has proved to be a useful, inexpensive diagnostic tool for the management of patients with autoimmune thyroid disease, mainly Hashimoto thyroiditis and Graves disease. In such cases, it has 35% to 84% sensitivity and 82% to 96% specificity for detecting and characterizing the disruption of thyroid tissue architecture 1 , 2 . Moreover, it can distinguish subgroups of patients with different clinical courses 3 and disease activity, 4 detect early subclinical thyroid dysfunction, 5 and predict the risk of the evolution of subclinical to overt hypothyroidism 6 , 7 .…”
mentioning
confidence: 99%
“…Frequency of thyroid gland function decrease was particularly pronounced in the group with significantly decreased echogenicity; even in 76% of patients a disfunction was found in the sense of sublinical or clinical hypothyreoidism. Other authors also found higher frequency of thyroid gland hypoechogenicity in persons with higher TSH values, in relation to the group of per- sons with normal values 3,[9][10][11][12][13] . It is stated that only 2.2% persons with normal ultrasound echogenicity suffer from subclinical hypothyreoidism.…”
Section: Discussionmentioning
confidence: 79%